Pengembangan Media Pembelajaran Bahasa Indonesia Berbasis Video Animasi pada Materi Teks Deskripsi Kelas VII MTs Swasta Darul Ulum Budi Agung - Fatimah Azzahra Dalimunthe; Tri Indah Kusumawati; Budiman Budiman (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2025)
This study was motivated by the low interest and skills of seventh-grade students at Darul Ulum Budi Agung Private Islamic Junior High School, which was caused by the use of uninteresting teaching methods and the lack of innovative learning media during classroom activities. This study aimed to develop animated video learning media for seventh-grade students' descriptive text material. The research methodology uses research and development with the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. The population in this study was seventh-grade students at MTs Swasta Darul Ulum Budi Agung, with a sample size of 30 students from class VII-1 and 30 students from class VII-5. Data collection was conducted through observation, interviews, validation tests, questionnaires, and documentation, then analyzed using SPSS V.26 software with normality tests, homogeneity tests, and t-tests to obtain valid and accurate results. The research results indicate that the developed animated video was deemed highly suitable by media experts (90%), language experts (84%), and subject matter experts (86%). The practicality of the animated video also received highly practical results, with 94% of teachers, 58% of control class students, and 92% of experimental class students responding positively. Additionally, the effectiveness of the animated video showed an improvement in students' writing skills, with an average of 67.66 for the control class and 84.83 for the experimental class in the effective category. This study demonstrates that animated videos can serve as an alternative teaching material that supports the learning process and leads to significant improvements in learning outcomes.